The other Face of Janus: Or the Mindset of Conservatism - Ebinç, Sait (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This article aims to analysis the attitudes and tendencies of conservatism,which has become current again with the rapid political and social changes that have occurred in the world in recent years, from both a historical and methodological perspective. The foundational concepts of this analysis are ideology, mentality, and tradition. The reason for selecting this mindset of concepts is based on the assumption that conservatism is a composite form of various tendencies. In this text, the relationship between conservative thought and other political ideologies and thoughts will be examined, along with the intellectual and conceptual coordinates of conservative thought. These determinations and definitions will be made in light of the following questions. Firstly, the arguments put forth by classical conservatism against the Cartesian world design of Enlightenment philosophy will be discussed. Secondly, the new forms that conservative ideology has adopted and the ways in which it interrelations with other ideologies will be explored. The focus of this discussion is whether conservative thought, as a political activity, possesses an original value system or whether these values institutionalized and transform into an attitude. Other questions in this discussion include whether conservatism is a tradition or a custom. A common question related to conservative thought is whether it originates from institutionalized action or if it is merely a cynical thought limited to reacting to and commenting on the ideas of other ideologies and ideologues as a reactionary contingency. Does conservatism have its own unique fundamental theory and thought? These questions will be reanalyzed within the framework of this discussion. Finally, this text will inquire whether conservative thought has universal validity everywhere or if it is limited to a reaction against the cultural, national, and historical context in which it exists. Answers to these questions will be sought in this text.